Optimized performance data transmission in Mobile IP networks - Gholizadeh, Somayyeh; Abdullah, Azizol; Othman, Mohamed; Mohd Hanapi, Zurina; Heydarian, Mohsen (Springer, 2014)
In a Mobile IP network (MIPN), nodes move. When a node moves, it may go away from other nodes and this decreases available bandwidth and data rate and increases the propagation delay of links. Therefore, nodes’ movement can decrease data delivery and handoff latency; these will reduce network efficiency. Suppose that an MIPN uses an optimal routing algorithm and transmits data from a source node to a destination node optimally. Nodes’ movement can violate the optimality of the data transmission and this will waste bandwidth and network resources. In this paper we present a new parametric optimal unicast multichannel routing algorithm that computes a domain for a mobile node and this domain will hold the optimality of data transmission and prevent network efficiency failure. Our new method determines an optimal domain for each mobile node and does not allow nodes to exit from that optimal domain. Simulation results show that our new method increases data rate and network efficiency.